Integrated programs for mothers with substance abuse issues: A systematic review of studies reporting on parenting outcomes - Niccols Alison; Milligan Karen; Sword Wendy; Thabane Lehana; Henderson Joanna; Smith Ainsley (BMC, 2012)
Abstract Background Integrated treatment programs (those that include on-site pregnancy-, parenting-, or child-related services with addiction services) were developed to break the intergenerational cycle of addiction, dysfunctional parenting, and poor outcomes for mothers and children, yet there has been no systematic review of studies of parenting outcomes. Objectives As part of larger systematic review to examine the effectiveness of integrated programs for mothers with substance abuse issues, we performed a systematic review of studies published from 1990 to 2011 with data on parenting outcomes. Methods Literature search strategies included online bibliographic database searches, checking printed sources, and requests to researchers. Studies were included if all participants were mothers with substance abuse problems at baseline, the treatment program included at least one specific substance use treatment and at least one parenting or child service, and there were quantitative data on parenting outcomes. We summarized data on parenting skills and capacity outcomes. Results There were 24 cohort studies, 3 quasi-experimental studies, and 4 randomized trials. In the three randomized trials comparing integrated programs to addiction treatment-as-usual (N = 419), most improvements in parenting skills favored integrated programs and most effect sizes indicated that this advantage was small, ds = -0.02 to 0.94. Results for child protection services involvement did not differ by group. In the three studies that examined factors associated with treatment effects, parenting improvements were associated with attachment-based parenting interventions, children residing in the treatment facility, and improvements in maternal mental health. Conclusions This is the first systematic review of studies evaluating the effectiveness of integrated programs on parenting. The limited available evidence supports integrated programs, as findings suggest that they are associated with improvements in parenting skills. However, more research is required comparing integrated programs to addiction treatment-as-usual. This review highlights the need for improved methodology, study quality, and reporting to improve our understanding of how best to meet the parenting needs of women with substance abuse issues.